Application of large-area avalanche photodiodes to energy-dispersive x-ray fluorescence analysis - Fernandes, L. M. P. (2001)
The performance of several large-area avalanche photodiodes (LAAPDs) for application to x-ray spectrometry at room temperature was investigated. Optimum detector performance was obtained for gains of about 50-70. Good energy linearity of the LAAPDs' response to x-rays was observed up to energies of about 25 keV. For this energy range the space charge effects are negligible for gains below 100-150. The energy resolutions obtained with LAAPDs can be better than those obtained with proportional counters. Our results indicate that the energy resolution of an LAAPD is better than that of a proportional counter only when the LAAPD maximum dark current is <300 nA. For this case, minimum detectable x-ray energies of about 1 keV are possible. Spatial non-uniformity is responsible for an absolute increase of 1-2% in energy resolution at 6 keV when illumination of the LAAPD is broadened from 1 mm diameter to full area. Counting rates up to 5 × 104 counts s-1 are possible without significant degradation of detector performance. Copyright © 2001 John Wiley & Sons, Ltd.